Ostinatos in Black-Atlantic traditions: generic-specific similarity and proximity. Issue 2 (4th May 2022) - Rahn, Jay
Abstract : Ostinatos of sub-Saharan Africa, South America, and the Caribbean are continually repeated rhythms also known as "timelines." Taking as a starting point the ostinato termed the "Standard Pattern, " generic and specific features of Black-Atlantic ostinatos are analyzed: in European-derived theory, these features correspond to the quantity and quality of musical intervals. Like the standard pattern, other ostinatos that have been employed in several Black-Atlantic traditions and comprise a rhythmic structure that corresponds to the structure of hyperdiatonic scales in contemporary European-derived pitch theory; other widespread ostinatos considered have a complementary, hyperpentatonic structure. Interpreted in terms of Gestalt grouping principles, both of these kinds of ostinatos maximize similarity and proximity . Other ostinatos of these traditions can be construed as variants of hyperdiatonic or hyperpentatonic ostinatos. Differences of similarity and proximity that these variants manifest are analyzed in terms of adjacent swaps, fusions and fissions, and moduli that encompass two or more ostinatos' least common multiples. In turn, similarity and proximity measures for rhythmic ostinatos are shown to parsimoniously clarify aspects of pitch relations, including the general notion of evenness, within 1- dimensional frameworks for pitch and time.